2011
DOI: 10.1162/jocn_a_00001
|View full text |Cite
|
Sign up to set email alerts
|

Phrase Length Matters: The Interplay between Implicit Prosody and Syntax in Korean “Garden Path” Sentences

Abstract: In spoken language comprehension, syntactic parsing decisions interact with prosodic phrasing, which is directly affected by phrase length. Here we used ERPs to examine whether a similar effect holds for the on-line processing of written sentences during silent reading, as suggested by theories of "implicit prosody." Ambiguous Korean sentence beginnings with two distinct interpretations were manipulated by increasing the length of sentence-initial subject noun phrases (NPs). As expected, only long NPs triggere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 50 publications
(110 reference statements)
7
40
0
4
Order By: Relevance
“…Since the CPS has been consistently found in studies investigating the processing of prosodic boundaries (B€ ogels et al, 2010;Hwang & Steinhauer, 2011;Isel et al, 2005;Mietz et al, 2008;Pauker et al, 2011;Steinhauer et al, 1999;Steinhauer, 2003) this result shows that the CPS appears at the closure of intonational phrases. The amplitudes of both CPS components were larger for the incongruent sentences compared to natural sentences.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Since the CPS has been consistently found in studies investigating the processing of prosodic boundaries (B€ ogels et al, 2010;Hwang & Steinhauer, 2011;Isel et al, 2005;Mietz et al, 2008;Pauker et al, 2011;Steinhauer et al, 1999;Steinhauer, 2003) this result shows that the CPS appears at the closure of intonational phrases. The amplitudes of both CPS components were larger for the incongruent sentences compared to natural sentences.…”
Section: Discussionmentioning
confidence: 58%
“…When the IPBs are not in the correct position to disambiguate garden-path sentences, a specific ERP response consisting of a biphasic N400 e P600 pattern can be found as demonstrated in several studies (Hwang & Steinhauer, 2011;Isel, Alter, & Friederici, 2005;Steinhauer et al, 1999;Steinhauer, 2003;Mietz, Toepel, Ischebeck, & Alter, 2008;Pauker, Itzhak, Baum, & Steinhauer, 2011;see B€ ogels et al, 2011 for a review), with the P600 component missing in some cases (B€ ogels, Schriefers, Vonk, Chwilla, & Kerkhofs, 2010). This pattern was found for words that disambiguated the sentence towards an interpretation that was not compatible with the syntactic analysis of the sentence, therefore leading to processing problems (B€ ogels et al, 2011).…”
mentioning
confidence: 91%
“…Concerning the impact of contextual prosodic information on prosodic phrasing, Hwang and Steinhauer (2011) used the CPS to demonstrate an influence of phrase length on (implicit) prosodic phrasing (which had previously been shown in behavioral production studies, see above). In a silent reading study on Korean they found that only longer sentence-initial constituents elicited a CPS, while no effect was found for short subject noun phrases.…”
Section: Introductionmentioning
confidence: 96%
“…Because the ERP component coincides with the closure of major prosodic phrases, it has been termed closure positive shift (CPS). The CPS has been found to indicate the processing of prosodic boundaries in various languages: in German (e.g., Pannekamp et al, 2005; Männel and Friederici, 2009), English (e.g., Itzhak et al, 2010; Steinhauer et al, 2010; Pauker et al, 2011), Dutch (e.g., Kerkhofs et al, 2007; Bögels et al, 2010), Japanese (Wolff et al, 2008), Chinese (Li and Yang, 2009) and Korean (Hwang and Steinhauer, 2011, implicit prosody).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos reportaram que o LAN e o ELAN opunham frases neutras, gramaticais, de frases contendo violações sintáticas: a morfossintaxe não estava adequada (concordância ou marcador de caso repetido) ou em sentenças contendo uma combinação de palavras inadequadas (e.g. uma palavra ou grupo de palavras aparecia em um contexto em que palavras de uma categoria sintática diferente eram esperadas -HAGOORT; LEVELT, 2009;HWANG;STEINHAUER, 2011).…”
Section: Componentes Comumente Encontrados Em Experimentos De Processunclassified